2020
DOI: 10.1007/s00586-020-06450-3
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral, intraspinal and other organ anomalies in congenital scoliosis

Abstract: Aims This study was undertaken to describe the pattern of vertebral, intraspinal and other organ anomalies in patients with congenital scoliosis and to determine the correlation between them. Methods Complete medical and radiological records of 227 consecutive patients with congenital scoliosis were analysed. The radiographs were examined for type of vertebral anomaly, location and severity of deformity. The median curve progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
3
9
0
1
Order By: Relevance
“…In all CS patients, 49.1% were typed as failure of formation, 19.5% as failure of segmentation, and 31.4% as mixed defects. This distribution was similar to that in previous studies [7,14,16,18,19]. We also found that failure of formation was significantly more common in male patients, whereas failure of segmentation or mixed defects were significantly more common in female patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In all CS patients, 49.1% were typed as failure of formation, 19.5% as failure of segmentation, and 31.4% as mixed defects. This distribution was similar to that in previous studies [7,14,16,18,19]. We also found that failure of formation was significantly more common in male patients, whereas failure of segmentation or mixed defects were significantly more common in female patients.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of intraspinal anomalies was 29.4%, which was in the range of previous studies [7,[12][13][14][16][17][18][19]. The most common associated anomaly of intraspinal defect was diastematomyelia, with an incidence of 19.3%, followed by syringomyelia (13.2%) and tethered cord (9.1%).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…For these reasons, osseous torticollis is likely to be overlooked especially if vertebral anomalies are not accompanied by other discernible congenital defects, such as vertebral defects, imperforate anus, tracheoesophageal fistula, and radial and renal dysplasia (VATER) syndrome; Klippel–Feil syndrome (vertebral fusion with prominent features such as low hairline, short neck, facial asymmetry, scoliosis, or spina bifida and genitourinary problems, heart abnormalities, or lung defects); Alagille syndrome; or Müllerian duct aplasia, renal aplasia/agenesis, and cervicothoracic somite dysplasia (MURCS) association. Vertebral anomalies increase instability risk and spinal cord encroachment and therefore should be considered in pediatric patients with abnormal head and neck posture to avoid potential neurologic injury [ 4 , 5 , 6 , 7 , 8 ]. If a correct diagnosis is confirmed, patients can receive proper management and clinicians can avoid pursuing unnecessary physical therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Будучи эмбриологической аномалией, ВДП часто сочетается с пороками развития мочеполовой, сердечно-сосудистой, скелетно-мышечной систем. Эти факторы играют важную роль при принятии решений о тактике лечения детей с ВДП [5].…”
unclassified